2023
DOI: 10.1186/s12943-023-01814-x
|View full text |Cite
|
Sign up to set email alerts
|

LINC02159 promotes non-small cell lung cancer progression via ALYREF/YAP1 signaling

Abstract: Lung cancer is the leading cause of cancer-related deaths worldwide. Long non-coding RNAs (lncRNAs) have emerged as key regulators of cancer development and progression, and as promising biomarkers for the diagnosis and prognosis of cancer. In this study, we identified a new lncRNA (LINC02159) that was upregulated in the tumor tissues and serum of non-small cell lung cancer (NSCLC) patients. We demonstrated that knockdown of LINC02159 inhibited NSCLC cell proliferation, migration, and invasion, but induced cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…ALYREF, an important m5C reader, has been proven to maintain mRNA stability [ 20 22 ]. To verify whether ALYREF is a functional m5C reader in lung cancer cells, we performed RIP assay with ALYREF antibody in H1650 and H1299 cells, and the RT-qPCR results showed that ALYREF could bind to EZH2 mRNA, suggesting that ALYREF might be the m5C reader (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…ALYREF, an important m5C reader, has been proven to maintain mRNA stability [ 20 22 ]. To verify whether ALYREF is a functional m5C reader in lung cancer cells, we performed RIP assay with ALYREF antibody in H1650 and H1299 cells, and the RT-qPCR results showed that ALYREF could bind to EZH2 mRNA, suggesting that ALYREF might be the m5C reader (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…LncRNAs not only regulate gene expression and participate in signal transduction pathways but also regulate epigenetic, transcriptional, and post-transcriptional modifications [ 45 ]. LncRNA expression is closely related to a variety of biological functions, including cell survival, cancer progression and metastasis [ 46 , 47 ]. Recent studies have shown that abnormal expression levels of lncRNAs are closely related to the pathology and prognosis of glioma [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and in vivo studies have identifiedthe RNA methyltransferase NSUN2 as primarily enzyme catalyzing m5C production in mRNAs, with m5C specifically recognized by the mRNA export adaptor ALYREF [ 46 ]. Recent research has linked ALYREF to the development of various tumors, including bladder cancer [ 47 , 48 ], breast cancer [ 49 ], neuroblastoma [ 50 ], hepatocellular carcinoma [ 51 , 52 ], glioblastoma [ 53 ], and non-small cell lung cancer [ 54 ]. These findings underscore the gene’s critical role in human cancer.…”
Section: Discussionmentioning
confidence: 99%